Purinoceptor Targeted Cytotoxicity of Adenosine Triphosphate-Conjugated Biogenic Selenium Nanoparticles in Human Colon Cancer Cells - Kandasamy Saravanakumar; Anbazhagan Sathiyaseelan; Xin Zhang; Soyoung Park; Myeong-Hyeon Wang (MDPI AG, 2022)
The adenosine triphosphate (ATP)-conjugated biogenic selenium nanoparticles (SeNPs) for P2 (purinoceptors) receptor-targeted anti-colon cancer activity were developed in this study. First, the SeNPs were synthesized using Trichoderma extracts (TE) and then conjugated with ATP to enhance their anticancer activity. The developed SeNPs had an oval crystalline structure with an average diameter size of 26.45 ± 1.71 d. nm, while the ATP-SeNPs were 78.6 ± 2.91 d. nm. The SeNPs contain Se, and less persistence of P while the ATP-SeNPs have high level of P, and Se in the energy-dispersive spectroscopy (EDS). Further, both nanoparticles exhibited larger sizes in the dynamic light scattering (DLS) analysis than in the transmission electron microscopy (TEM) analysis. The DLS and Fourier transform infrared spectroscopy (FTIR) results provide evidence that the amine group (-NH2) of ATP might bind with the negatively charged SeNPs through covalent bonding. The IC50 concentration was 17.25 ± 1.16 µg/mL for ATP-SeNPs and 61.24 ± 2.08 µg/mL against the caco-2 cell line. The IC50 results evidenced the higher cytotoxicity of ATP-SeNPs in the caco-2 cell line than in HEK293 cells. ATP-SeNPs trigger the anticancer activity in the caco-2 cell line through the induction of mitochondrial membrane potential (MMP) loss and nucleus damage. The biocompatibility test of hemolysis and the egg CAM assay confirmed the non-toxicity of these nanoparticles. Overall, the results proved that the newly developed ATP-SeNPs exhibited higher cytotoxicity in the caco-2 cell line than SeNPs. However, further molecular and in vivo experiments are required to develop the ATP-SeNPs as a candidate drug for cancer-targeted therapeutics.